2017
DOI: 10.3389/fnmol.2017.00209
|View full text |Cite
|
Sign up to set email alerts
|

Cold Temperature Encoding by Cutaneous TRPA1 and TRPM8-Carrying Fibers in the Mouse

Abstract: Previous research identified TRPM8 and TRPA1 cold transducers with separate functions, one being functional in the non-noxious range and the second one being a nociceptive transducer. TRPM8-deficient mice present overt deficits in the detection of environmental cool, but not a lack of cold avoidance and TRPA1-deficient mice show clear deficits in some cold nocifensive assays. The extent of TRPA1's contribution to cold sensing in vivo is still unclear, because mice lacking both TRPM8 and TRPA1 (DKO) were descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 31 publications
6
33
1
1
Order By: Relevance
“…TRPA1 was initially proposed to be involved in noxious cold sensing (Story et al 2003) but recent reports have questioned its role, hypothesizing that it might be regulating cold sensitivity indirectly, rather than acting as a cold-sensing receptor (Lolignier et al 2016;Yarmolinsky et al 2016;Winter et al 2017). If TRESK and TRPA1 are partially co-expressed in some neurons, one would expect an increase in the responses triggered by TRPA1 activation but, to our surprise, we observed the opposite effect despite TRPA1 mRNA expression being unchanged.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…TRPA1 was initially proposed to be involved in noxious cold sensing (Story et al 2003) but recent reports have questioned its role, hypothesizing that it might be regulating cold sensitivity indirectly, rather than acting as a cold-sensing receptor (Lolignier et al 2016;Yarmolinsky et al 2016;Winter et al 2017). If TRESK and TRPA1 are partially co-expressed in some neurons, one would expect an increase in the responses triggered by TRPA1 activation but, to our surprise, we observed the opposite effect despite TRPA1 mRNA expression being unchanged.…”
Section: Discussioncontrasting
confidence: 56%
“…An increase in cold sensitivity has also been reported in TRESK KO mice using the acetone test (Guo et al 2019). In our study, the fraction of C-fibres activated by cold (C-MHC and C-MC; 58% in WT mice) was higher than other reports (35-45%), which could be due to the smaller number of fibres sampled compared to other studies Noël et al 2009;Pereira et al 2014;Winter et al 2017) but, as occurred after deletion of other K 2P channels, the fraction of cold-sensitive C-fibres was enhanced in TRESK KO mice compared to WT animals. Interestingly, the larger fraction of cold-sensitive C-MC fibres (37%) in KO animals compared to WT animals (20%) suggests that, in physiological conditions, TRESK silences a population of neurons that would be normally activated at lower temperatures.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…First, in addition to Trpm8, there is another cold-activated Trp channel known as transient receptor potential ankyrin 1 (Trpa1) which is considered to be a noxious cold receptor [52]. Interestingly, Trpm8 and Trpa1 appear to function in both complementary and synergistic fashion to detect environmental innocuous and noxious cold [52]. Winter et al (2017) found that the lack of Trpm8 and Trpa1 led to a striking reduction in cold avoidance behavior in mice [52].…”
Section: Demonstrated Thatmentioning
confidence: 99%